Trachyspermum ammi - Bairwa, Ranjan; Sodha, R. S.; Rajawat, B. S. (Pharmacognosy Reviews, 2012)
Trachyspermum ammi commonly known as ‘Ajwain’ is distributed throughout India and is mostly cultivated in Gujarat and Rajasthan. The fruit possesses stimulant, antispasmodic and carminative properties and is used traditionally as an important remedial agent for flatulence, atonic dyspepsia, diarrhea, abdominal tumors, abdominal pains, piles, and bronchial problems, lack of appetite, galactogogue, asthma and amenorrhoea. Medicinally, it has been proven to possess various pharmacological activities like antifungal, antioxidant, antimicrobial, antinociceptive, cytotoxic, hypolipidemic, antihypertensive, antispasmodic, broncho-dilating actions, antilithiasis, diuretic, abortifacient, antitussive, nematicidal, anthelmintic and antifilarial. Further, studies reveal the presence of various phytochemical constituents mainly carbohydrates, glycosides, saponins, phenolic compounds, volatile oil (thymol, γ-terpinene, para-cymene, and α- and β-pinene), protein, fat, fiber and mineral matter containing calcium, phosphorous, iron and nicotinic acid. These studies reveal that T. ammi is a source of medicinally active compounds and have various pharmacological effects; hence, it is encouraging to find its new therapeutic uses.
Keywords: Apiaceae; antimicrobial; ajwain; fruit (seed); trachyspermum ammi